Optimalisasi Rekam Medis Kesehatan: Pengembangan Sistem Informasi Siredi Berbasis Website dengan Framework Laravel - Putri, Tiara Eka; Apriyandi, Dedek Tegar; Ariani, Selvia (Universitas Bengkulu, 2024)
The Medical Record Information System (SIREDI) is an innovative solution for managing medical data within the healthcare environment. In the development context of SIREDI, using the Laravel framework plays a crucial role in enhancing the efficiency, security, and accessibility of medical information. Previous research has highlighted the integration of medical record information systems with cloud technology, user requirement analysis, and usability evaluation. By focusing on integrating modern technology, improving usability, and effective data management, the development of SIREDI aims to provide the best and sustainable solution for managing medical records in the Indonesian healthcare setting. It is hoped that SIREDI will serve as an inspirational example, providing significant benefits to the healthcare industry in the future.